Convergence Analysis of a Weak Galerkin Finite Element Method on a Bakhvalov-Type Mesh for a Singularly Perturbed Convection-Diffusion Equation in 2D (Advances in Applied Mathematics and Mechanics, 2025)
In this paper, we propose a weak Galerkin finite element method (WG) for solving singularly perturbed convection-diffusion problems on a Bakhvalov-type mesh in 2D. Our method is flexible and allows the use of discontinuous approximation functions on the mesh. An error estimate is developed in a suitable norm, and the optimal convergence order is obtained. Finally, numerical experiments are conducted to support the theory and to demonstrate the efficiency of the proposed method.